Evaluation of Changes in Functional Status in the Year After Aortic Valve Replacement - Kim, Dae Hyun (JAMA Intern Med, 2019)
IMPORTANCE: Functional status is a patient-centered outcome that is important for a meaningful gain in health-related quality of life after aortic valve replacement. OBJECTIVE: To determine functional status trajectories in the year after transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR). DESIGN, SETTING, AND PARTICIPANTS: A prospective cohort study with a 12-month follow-up was conducted at a single academic center in 246 patients undergoing TAVR or SAVR for severe aortic stenosis. The study was conducted between February 1, 2014, and June 30, 2017; data analysis was performed from December 27, 2017, to May 7, 2018. EXPOSURES: Preoperative comprehensive geriatric assessment was performed and a deficit-accumulation frailty index (CGA-FI) (range, 0-1; higher values indicate greater frailty) was calculated. MAIN OUTCOMES AND MEASURES: Telephone interviews were conducted to assess self-reported ability to perform 22 activities and physical tasks at 1, 3, 6, 9, and 12 months after the procedure. RESULTS: Of the 246 patients included in the study, 143 underwent TAVR (74 [51.7%] women; mean [SD] age, 84.2 [5.9] years), and 103 underwent SAVR (46 [44.7%] women; age, 78.1 [5.3] years). Five trajectories were identified based on functional status at baseline and during the follow-up: from excellent at baseline to improvement at follow-up (excellent baseline-improvement), good (high baseline-full recovery), fair (moderate baseline-minimal decline), poor (low baseline-moderate decline), and very poor (low baseline-large decline). After TAVR, the most common trajectory was fair (54 [37.8%]), followed by good (33 [23.1%]), poor (21 [14.7%]), excellent (20 [14.0%]), and very poor (12 [8.4%]) trajectories. After SAVR, the most common trajectory was good (39 [37.9%]), followed by excellent (38 [36.9%]), fair (20 [19.4%]), poor (3 [2.9%]), and very poor (1 [1.0%]) trajectories. Preoperative frailty level was associated with lower probability of functional improvement and greater probability of functional decline. After TAVR, patients with CGA-FI level of 0.20 or lower had excellent (3 [50.0%]) or good (3 [50.0%]) trajectories, whereas most patients with CGA-FI level of 0.51 or higher had poor (10 [45.5%]) or very poor (5 [22.7%]) trajectories. After SAVR, most patients with CGA-FI level of 0.20 or lower had excellent (24 [58.5%]) or good (15 [36.6%]) trajectories compared with a fair trajectory (5 [71.4%]) in those with CGA-FI levels of 0.41 to 0.50. Postoperative delirium and major complications were associated with functional decline after TAVR (delirium present vs absent: 14 [50.0%] vs 11 [13.4%]; complications present vs absent: 14 [51.9%] vs 19 [16.4%]) or lack of improvement after SAVR (delirium present vs absent: 27 [69.2%] vs 31 [81.6%]; complications present vs absent: 10 [62.5%] vs 69 [79.3%]). CONCLUSIONS AND RELEVANCE: The findings suggest that functional decline or lack of improvement is common in older adults with severe frailty undergoing TAVR or SAVR. Although this nonrandomized study does not allow comparison of the effectiveness between TAVR and SAVR, anticipated functional trajectories may inform patient-centered decision making and perioperative care to optimize functional outcomes.